Tracking single baculovirus retrograde transportation in host cell via quantum dot-labeling of virus internal component - Li Wen; Zhen-Hua Zheng; An-An Liu; Cheng Lv; Li-Juan Zhang; Jian Ao; Zhi-Ling Zhang; Han-Zhong Wang; Yi Lin; Dai-Wen Pang (Journal of Nanobiotechnology, 2017)
Abstract Background Quantum dot (QD)-based single virus tracking has become a powerful tool for dissecting virus infection mechanism. However, only virus behaviors at the early stage of retrograde trafficking have been dynamically tracked so far. Monitoring of comprehensive virus retrograde transportation remains a challenge. Results Based on the superior fluorescence properties of QDs and their labeling of virus internal component, the dynamic interactions between baculoviruses and all key transportation-related cellular structures, including vesicles, acidic endosomes, actins, nuclear pores and nuclei, were visualized at the single-virus level. Detailed scenarios and dynamic information were provided for these critical interaction processes. Conclusions A comprehensive model of baculovirus retrograde trafficking involving virus endocytosis, fusion with acidic endosome, translocation to nuclear periphery, internalization into nucleus, and arriving at the destination in nucleus was proposed. Thus the whole retrograde transportation of baculovirus in live host cells was elucidated at the single-virus level for the first time.